A JOURNEY TO THE QUALITATIVE WONDERLAND: LESSONS LEARNED FOR NOVICE RESEARCHERS - Tsai, Kuan Chen (Jurnal Ilmiah Peuradeun, 2014)
It is believed that through a journey of being a good researcher, it is beneficial to appreciate two different values drawing form two opposite paradigms, which in turn familiarizing oneself with two distinct conceptual frameworks thereby strengthening individual’s research capacity. In this paper, a novice qualitative researcher shares four lessons learned from the process of conducting his first qualitative study. The lessons are: (1) Do your homework on the literature; (2) Carefully read regulations of Institutional Review Board; (3) Any confusion, ask the experts first; (4) If possible, try to use qualitative data analysis software; and (5) Reflect and challenge your assumptions all the time.